Biochar mitigates soil–rice accumulation of highly bioavailable heavy metals from atmospheric deposition - Huang, Zhaoqin; Du, Buyun; Sun, Ting; Ji, Dongliang (Frontiers in Environmental Science, 2025)
Little is known regarding the uptake of heavy metal(loid)s (HMs) by crops from atmospheric deposition. In this study, we examined the uptake and transport of HMs (copper, zinc, arsenic, cadmium, and lead) in rice plants through both root and foliar pathways, and the reduction of HMs in rice resulting from soil biochar applications. Our findings indicate that HMs from dust and rainfall were more mobile and bioavailable than those from slag, significantly affecting the soluble and exchangeable fractions of HMs in the soil, soil solution, and fractions detected by the diffusive gradients in thin films (DGT) technique. Rice plants exhibited a preference for absorbing atmospherically deposited HMs through both foliar and root pathways; however, the efficiency of HM uptake and translocation rates via direct foliar uptake was lower than that of root uptake from the soil. The application of biochar was found to decrease HM (Cu, Zn, Pb, and Cd) concentrations in soil mobile fractions, soil solutions, and DGT extractions, with the exception of As; this demonstrates an effective method to mitigate HM accumulation in rice. This study highlights the high risk of crop contamination in areas with high atmospheric HM loads and suggests that reducing atmospheric HM deposition and implementing soil remediation can mitigate ecological risks.